Research priorities for the management of broken bones of the upper limb in people over 50: a UK priority setting partnership with the James Lind Alliance. Issue 12 (15th December 2019) - Sheehan, Warren J; Williams, Mark A; Paskins, Zoe; Costa, Matthew L; Fernandez, Miguel Antonio; Gould, Jenny; Bell, Philip; Baird, Liz; Grant, Richard; Ellis, Patricia; White, Catherine; Arnel, Laura; et al.
Abstract : Objective: To determine research priorities for the management of broken bones of the upper limb in people over 50, which represent the shared priorities of patients, their families, carers and healthcare professionals. Design/setting: A national (UK) research priority setting partnership. Participants: People aged 50 and over who have experienced a fracture of the upper limb, carers involved in their care, family and friends of patients, healthcare professionals involved in the treatment of these patients. Methods: Using a multiphase methodology in partnership with the James Lind Alliance over 15 months (September 2017 to December 2018), a national scoping survey asked respondents to submit their research uncertainties. These were amalgamated into a smaller number of research questions. The existing evidence was searched to ensure that the questions had not already been answered. A second national survey asked respondents to prioritise the research questions. A final shortlist of 25 questions was taken to a multi-stakeholder workshop where a consensus was reached on the top 10 priorities. Results: There were 1898 original uncertainties submitted by 328 respondents to the first survey. These original uncertainties were refined into 51 research questions of which 50 were judged to be true uncertainties following a review of the research evidence. There were 209 respondents to the second (interim prioritisation) survey. The top 10 priorities encompass a broad range of uncertainties in management and rehabilitation of upper limb fractures. Conclusions: The top 10 UK research priorities highlight uncertainties in how we assess outcomes, provide information, achieve pain control, rationalise surgical intervention, optimise rehabilitation and provide psychological support. The breadth of these research areas highlights the value of this methodology. This work should help to steer research in this area for the next 5–10 years and the challenge for researchers now is to refine and deliver answers to these research priorities.